Industry of Acrylic, Woven - Patterned Blanket in - (Kadhimiya & Fateh) Factories for (2009-2015) A Comparative Study - Redha Al-Salamy, Intesar Hassoon (European Journal of Sustainable Development, 2017)
The fabric industry is one of the vital field for many of third world countries, it has great influence at the economic growth, fabric field has major role in the infrastructure of Iraqi industries ,so to step up a head we must expand this kind of industry and produce high quality goods , like many other fields ,the fabric industry is a blending of two important factors, agriculture & animal resources, the fabric industry represent start push towards the industrial transformation process , Therefore, the study consist of two topics , the first one explores the historical evolution of the general company of fabric and leather industries. (Kadhimiya & Fateh) factories belongs to the general company. The second topic shows the statistical and quantity analysis for elements of industrial localization of blanket industry in Baghdad for (2009-2015), the result of study indicate there are many indicators make these factories are Ideal and adequate to expand and flourish in area of study, those indicators are: the availability of qualified workers , positive statistical results, finally the study was culminated by conclusions and recommendations . Keywords: Fateh Factory, Kadhimiya Factory , Acrylic - patterned blanket , Woven blanket